The HLA landscape of Colombia: a high-resolution analysis of 11,576 blood donors - Muñoz, Ana Luisa; Uricoechea, Daniel; Gómez, Lina Andrea; Argote-Bérdugo, Hernán; Bula, Johan; Rueda, María Alejandra; Rueda, Miguel Germán; Briceño, Ignacio (Frontiers in Immunology, 2025)
BackgroundThe highly polymorphic Human Leukocyte Antigen (HLA) system is critical for adaptive immunity and determines compatibility in transfusion and transplantation medicine. Admixed Latin American populations, such as Colombia’s trihybrid population, possess unique HLA diversity that remains poorly characterized at high resolution.MethodsWe performed high-resolution HLA typing on 11,576 Colombian blood donors from two distinct regions: the Andean and Caribbean. We analyzed allele and haplotype frequencies, Hardy-Weinberg equilibrium, linkage disequilibrium (LD), and compared genetic distances with global populations via PCA and UPGMA clustering.ResultsWe identified 565 alleles and 17,317 unique haplotypes, revealing extreme diversity. A few alleles dominated each locus, yet the top 20 haplotypes had a cumulative carrier frequency of only 3.17%, highlighting a fragmented haplotype landscape. Strong LD was observed between class I and II loci (HLA-A~DQB1), indicating conserved extended haplotypes. Genetically, the Colombian cohorts formed a tight cluster, showing closest affinity to Indigenous Chilean populations, suggesting a shared Andean background.DiscussionThis study provides the first large-scale, high-resolution HLA map of Colombia, capturing the extensive immunogenetic diversity of an admixed Latin American population. Our findings are vital for improving transplant matching, understanding population-specific disease risks, and advancing equitable genomic medicine in the region.